Transition to a new era with light-based hydrogen production for a carbon-free society: An overview - Acar, Canan; Bicer, Yusuf; Demir, Murat Emre; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
This study discusses the transitional solutions with light-based hydrogen production for a carbon-free or low-carbon future. With a particular focus on the cutting-edge research activities at the Clean Energy Research Laboratory (CERL), some light-based innovative hydrogen production systems are discussed thoroughly. At the CERL, the main motivation is to achieve sustainability via a 3S approach, which is the source, system, and service. Therefore, clean, efficient, affordable, and reliable hydrogen production is seen as the first step towards the transition to a carbon-free future. With this goal in mind, the initial research activities at the CERL cover PV-electrolysis, photocatalysis, and photoelectrochemical cells for sustainable light-based hydrogen production. In the following steps, towards hybridization and system integration, various effective multigeneration systems are designed, built, and tested at the CERL. These multigeneration systems not only enhance the solar spectrum utilization, but also provide additional valuable system products such as electricity, heat, Cl-2, NaOH, clean water, and ammonia. Better resource utilization decreases system costs, enhances efficiencies, and certainly lowers the negative environmental footprint. The innovative hydrogen production systems designed at the CERL do not require additional chemicals like most of the photocatalytic systems, and as a result, they have less damage to the limited clean water resources of our planet. Besides, at the CERL, numerous novel systems are developed and tested to produce hydrogen from wastewaters. All of these systems are capable of producing outputs that are widely needed across the globe, which highlights the importance of the research currently taken place at the CERL. (C) 2019 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrogen production; Solar energy; Clean energy: energy; Exergy; Efficiency; Sustainability; RENEWABLE HYDROGEN; CLIMATE-CHANGE; ENERGY SYSTEM; IMPACTS; WATER; Chemistry; Electrochemistry; Energy & Fuels